Perceived analogical communication in design teams: Development and validation of a scale. (March 2020) - Graff, Daniel; Meslec, Nicoleta; Clark, Mark A.
Abstract : Analogies have been shown to play a key role in design collaboration. However, research has been largely limited to the analogy itself and how it is used, overlooking the impact of analogy from the recipients' perspective. This is a critical aspect, considering the imperfect information transfer between members in design teams. We address this gap by developing a measure of perceived analogical communication in teams, focusing on the interpretation of the use of analogy in internal design team communications. We test the resulting scale across 3 samples, totalling 252 multi-disciplinary teams with 1182 team members. Results show that the scale is an internally consistent, distinct construct, and holds predictive validity for relevant design team processes and outcomes. Highlights: The use of analogies in communication is important for the performance of design teams. The receiver's perception of the analogy is important. Perceived analogies reduce conflict in teams, which in turn improves their outcome.